Sistemas de culturas em plantio direto adaptados à pequena propriedade relacionados com a erosão e atributos de um argissolo vermelho - Lanzanova, Mastrângello Enivar (2009)
Considering soil management systems, are rare the research projects that are carried on by a time period long enough to several soil attributes may be expressed conveniently. The no-till system influences several soil attributes and in this context, this study aimed to evaluate the effect of tillage system with the use of cover crops in winter and summer, on some chemical and physical soil attributes after long-term adoption of the system. Also aimed to evaluate the corn grain yield, dry matter production and carbon by different cropping systems, the stock of organic carbon and nitrogen in the soil, and also to investigate the no-till effect in reducing soil loss and water compared with the soil in its original state and the soil kept permanently uncovered and exposed to climate action. The experiment began in 1991 in a soil classified as Paleudalf. The experiment uses, since 2001, as treatments, the crop systems described as follows: (1) Corn (Zea mays L.) + jack bean (Canavalia ensiformis DC) / Soybean (Glycine max (L.) Merr.) (MFP), (2) Soil Permanently Discovered (SDES), (3) Maize / fallow / soybean / fallow (POU), (4) Corn / ryegrass (Lolium multiflorum Lam) + common vetch (Vicia sativa) / soybean / common vetch + rye grass (ryegrass) (AZEV), (5) Maize + velvet bean (Styzolobium cinereum) / Soybean (MUC), (6) Native pasture (CNA), and (7) Maize / oilseed radish (Raphanus sativus L. var. oleiferus Metzg.) / Soybean / oilseed radish (NFO). The results showed that the soil permanently uncovered causes severe damages in attributes of soil fertility, mainly the content of organic matter and soil potassium. The analysis of only soil pH was not sufficient to characterize the state of soil acidity, it is necessary to know the concentration of other components such as aluminum exchangeable and levels of calcium + magnesium. The residual effect of lime application before the implementation of no-tillage, in the value of pH, exchangeable aluminum and phosphorus, exceed 16 years. There was a direct relationship between the pH of the soil and its organic matter content, and an inverse relationship between the value of pH and aluminum, with the increasing depth in the soil for all treatments. For the physical attributes evaluated, the results showed that the maintenance of the soil surface permanently unprotected promotes rapid degradation of them, with formation of surface sealing and reduced water infiltration. The soil total porosity and macroporosity, 0.0.- 0.10 m depth, were closely related. The resistance penetration showed higher resistance in the surface layer (up to 0.03 m) of treatment SDES, and NFO presented the highest values at depths of 0.16 and 0.18 m. Lower rates of water infiltration in soil were observed over all time periods (5, 10, 15, 20, 30, 60, 90 and 120 min) studied, in the treatments SDES and CNA, while the others stay constantly above these and similar. No-tillage with the use of cover crops, after a long period of use, was efficient in maintaining physical attributes, such as density and porosity of soil conditions favorable to plant growth, while other attributes that improved, as the rate of water infiltration, compared with its initial condition of native pastures. Regarding the production of corn, no-till system using green manure in summer and winter, after a long period, provided higher yields than systems that use fallow. The soil cultivation from a native condition determined losses in their organic carbon content, but this can be recovered with the use of no-tillage system with a high input of plant residues rich in carbon and nitrogen. Maintenance of the surface soil exposed to erosion for a long period, caused significant losses in its carbon content and total nitrogen. No-tillage with the use of summer green manures (velvet bean) and winter (rye + vetch), promoted increases in the organic carbon stock in the soil layer of 0.0 0.05 m in relation to their initial stock. However, the layer from 0.0 to 0.20 m depth, none crop system has reached the rated values found in the reference treatment, in this case, the native grasses. The results for soil and water conservation were amazing. The maintenance of soil surface exposed rain erosive action for a long period, led to the progressive loss of a soil layer of about 1 cm per year, equivalent to approximately 150 t ha-1 of soil. No-tillage had, in some years, water losses smaller than those found under native pasture. Compared with the losses sustained in soil continuously discovered, the reduction of soil loss by notillage system reached 99.9%. No-tillage was more effective in reducing soil loss than the loss of water in crop systems. The wettest and most erosive rains occurred in the months from October to March, coinciding with the period for the development and the grain harvest of summer crops, for the conditions of Santa Maria, RS.